mRNA translation from an antigen presentation perspective: A tribute to the works of Nilabh Shastri - Apcher, Sebastien; Tovar-Fernadez, Maria; Ducellier, Sarah; Thermou, Aikaterini; Nascimento, Megane; Sroka, Ewa; Fahraeus, Robin (Molecular immunology, 2022)
The field of mRNA translation has witnessed an impressive expansion in the last decade. The once standard model of translation initiation has undergone, and is still undergoing, a major overhaul, partly due to more recent technical advancements detailing, for example, initiation at non-AUG codons. However, some of the pioneering works in this area have come from immunology and more precisely from the field of antigen presentation to the major histocompatibility class I (MHC-I) pathway. Despite early innovative studies from the lab of Nilabh Shastri demonstrating alternative mRNA translation initiation as a source for MHC-I peptide substrates, the mRNA translation field did not include these into their models. It was not until the introduction of the ribo-sequence technique that the extent of non-canonical translation initiation became widely acknowledged. The detection of peptides on MHC-I molecules by CD8 + T cells is extremely sensitive, making this a superior model system for studying alternative mRNA translation initiation from specific mRNAs. In view of this, we give a brief history on alternative initiation from an immunology perspective and its fundamental role in allowing the immune system to distinguish self from non-self and at the same time pay tribute to the works of Nilabh Shastri.
Keywords: RNA, Messenger; prezentace antigenu; Receptors for Activated C Kinase; receptory pro aktivovanou kinasu C; Protein Biosynthesis; proteosyntéza; Antigen presentation; Histocompatibility Antigens Class I; MHC antigeny I. třídy; CD8-Positive T-Lymphocytes; Animals; lidé; CD8-pozitivní T-lymfocyty; MHC class I pathway; Humans; zvířata; Peptides; peptidy; Antigen Presentation; mRNA translation initiation; messenger RNA